Analisa Kualitas Produk, Harga, dan Lokasi Melon Hidroponik terhadap Kepuasan Konsumen di Kota Kediri - Prastiwi, Rika; Talkah, Abu; Suparno, Suparno (Universitas Islam Kadiri, 2025)
Hydroponic farming, especially melons, is gaining popularity in Indonesia along with the increasing demand for food. Despite the increasing interest and adoption of this method, the level of consumer satisfaction with hydroponic melons is still a problem that needs to be researched, especially in Kediri City. Therefore, it is necessary to examine product quality, price, and location on consumer satisfaction at Omah Melon Kediri and Sanjaya and TT Hydroponics in the Kediri city area. The analysis techniques used in this study are classical assumptions, multiple linear regression, analysis of the coefficient of determination (R2), F test, and t test. The results of the study concluded that Product Quality (X1), Price (X2) and Location (X3) simultaneously affect Consumer Satisfaction (Y) at Omah Melon Kediri and Sanjaya and TT Hydroponics. Product Quality (X1) has no effect on Consumer Satisfaction (Y) both at Omah Melon Kediri and Sanjaya and TT Hydroponics. Price (X2) has an effect on Customer Satisfaction (Y) both at Omah Melon Kediri and Sanjaya and TT Hydroponics. Location (X3) affects customer satisfaction (Y) at Omah Melon Kediri, but location (X3) has no effect on customer satisfaction (Y) at Sanjaya and TT Hydroponics.